Assessment of Infection Control and Occupational Safety Procedures at Blood Bank in Zliten Medical Center - Ahmed A Algdar; Mahfoud M. Alwalid; Walid Faraj Naamat (Journal of Scientific and Human Dimensions, 2026)
This descriptive cross-sectional study aimed to evaluate infection control and occupational safety procedures among the technical staff at the Blood Bank in Zliten Medical Central. The study sample included all engineers and technicians at the facility (N = 60). Data were collected using standardized questionnaires and administrative checklists designed to assess training, preventive measures, and operational policies. The results showed a stark contrast. Indicators revealed a complete absence (100%) of orientation and training programs for new employees, and a total lack of records documenting occupational exposure incidents or written policies for post-exposure procedures. A severe shortage (100%) of basic personal protective equipment, such as medical gloves, goggles, and filter masks, was also found. Conversely, the study recorded excellent technical compliance (100%) in re-examining and confirming samples that initially tested positive, with an 85% vaccination rate against blood borne viruses. Inferential analyses using the chi-square test (χ²) demonstrated that the decision to continue dispensing blood at a rate of 80% when testing reagents were scarce (p = 0.067) is a general operational behavior dictated by the critical medical nature and the pressure of need within the municipality. Meanwhile, the lack of vaccinations was biologically associated with new employees (p = 0.028). The study concludes that urgent intervention from health authorities is necessary to provide protective equipment and activate infection control committees and written policies to ensure the safety and well-being of medical staff and patients.